Bioprospective potentials of endophytic fungi penicillium SPP isolated from leaves of azadirachta indica (A. JUSS) - Abubakar, salisu; Wusa Ndana, Rebeccah; Samuel Afolabi, Abolade (International Journal of Biological Research, 2017)
The focus of this research work was to isolates and identify endophytic fungi from young leaves and stems (twig) of Azadirachta indica, family (Meliaceae) for the production and assay of the produced secondary metabolites. Altogether 126 segments were used, of which 63 segments each from leaves and stems (twig) tissues were screened, using modified surface sterilization techniques. A total of 12 species of endophytic fungi were purely isolated, Penicillium spp was randomly selected for the extraction and evaluation of its secondary metabolites. The eluent collected from column chromatography mixture of ethylacetate and n- hexane (50:50v/v) was phytochemically screened, and the results showed the presence of saponins, flavonoids and phenols. Based on disc diffusion method of sensitivity, the eluent possessed some degree of antibacterial and antifungal activities. In addition, in-vitro antioxidant potentiality of the eluent was also evaluated using 2, 2- Diphenyl-1-picrylhydrazyl radical (DPPH, Sigma Aldrich). Statistical package for social science (SPSS 3/93) software was used to analyze the results using one way Analysis of Variance (ANOVA), which revealed no significant difference, on the effect of concentrations of eluent on test organisms but the eluent showed significant difference on scavenging free radicals at a critical value (p >0.05).